Phylogeography and karyotypic evolution of some Deuterodon species from southeastern Brazil (Characiformes, Characidae, Stethaprioninae) - Igor Henrique Rodrigues-Oliveira; Pierre Rafael Penteado; Rubens Pasa; Fabiano Bezerra Menegídio; Karine Frehner Kavalco (Genetics and Molecular Biology, 2023)
Abstract Deuterodon is a genus of the subfamily Stethaprioninae, a group of Neotropical fish known as tetras. Deuterodon hastatus represents a species complex, which is supported by cytogenetic and molecular data. In this study, we show the results of comparative evolutionary analyses of the ATP synthase subunit 6 gene in four Deuterodon species, in addition to ribosomal markers (18S rDNA and 5S rDNA), of a new population of the D. hastatus species complex from the Angra dos Reis/RJ region. The study population comprised a new cytotype, which we refer to as cytotype D, in D. hastatus, with 2n = 50 = 6M+8SM+8ST+28A. We obtained three different clades of D. hastatus in our phylogeny, one of them composed only by specimens of cytotype D. By using molecular clock dating, we observed that the radiation of Deuterodon from southeastern Brazil seemed to be associated with neotectonic events that occurred during the Miocene-Pliocene and Pliocene-Pleistocene transitions, marked by the capture of headwater streams and marine transgressions. The results obtained reinforce the idea that D. hastatus is a species complex, and at least three evolutionary significant units were identified in this group.